Weather or not? The role of international sanctions and climate on food prices in Iran - Zamanialaei, Maryam; Brown, Molly E.; McCarty, Jessica L.; Fain, Justin J. (Frontiers in Sustainable Food Systems, 2023)
The agricultural sector in Iran is one of the three main sectors of the economy, and plays an important role in food supply, social welfare, and gross domestic productivity. Moisture availability is also a big limitation on Iran’s agricultural production. Across most of the country, the climate is arid or semi-arid, with long-run average annual rainfall estimates ranging from 200 to 230 millimeters per year. Iterative and mounting sanctions on Iran by the international community have seriously eroded Iran’s access to agricultural technology and resources to support a growing population. The scarcity of resources have affected food production, which has challenged the ability of Iran to provide adequate food for the population. The aim of this study was to analyze the influence of inflation, international sanctions, weather disturbances, and domestic crop production on the price of rice, wheat and lentils from 2010 to 2021 in Iran. Data were obtained from the statistical yearbooks of the Ministry of Agriculture in Iran, Statistical Center of Iran, and the Central Bank of Iran. We analyzed econometric measures of food prices, including CPI, food inflation, subsidy reform plan and sanctions to estimate economic relationships. After deflating the food prices through CPI and detrending the time series to resolve the non-linear issue, we used monthly Climate Hazards group Infrared Precipitation with Stations (CHIRPS) precipitation data to analyze the influence of weather disturbances on food prices. Our statistical modeling framework found that the monthly precipitation on domestic food prices, and ultimately food access, in the country is much less important than the international sanctions, lowering Iran’s productive capability and negatively impacting its food security.